Raised atmospheric CO2 levels and increased N deposition cause shifts in plant species composition and production in Sphagnum bogs - Berendse, Frank; van Breemen, Nico; Rydin, HÅkan; Buttler, Alexandre; Heijmans, Monique; Hoosbeek, Marcel R.; Lee, John A.; Mitchell, Edward; Saarinen, Timo; Vasander, Harri; Wallén, Bo (My University, 2001)
Part of the missing sink in the global CO2 budget has been attributed to the positive effects of CO2 fertilization and N deposition on carbon sequestration in Northern Hemisphere terrestrial ecosystems. The genus Sphagnum is one of the most important groups of plant species sequestrating carbon in temperate and northern bog ecosystems, because of the low decomposability of the dead material it produces. The effects of raised CO2 and increased atmospheric N deposition on growth of Sphagnum and other plants were studied in bogs at four sites across Western Europe. Contrary to expectations, elevated CO2 did not significantly affect Sphagnum biomass growth. Increased N deposition reduced Sphagnum mass growth, because it increased the cover of vascular plants and the tall moss Polytrichum strictum. Such changes in plant species composition may decrease carbon sequestration in Sphagnum-dominated bog ecosystems.
Keywords: bogs; carbon dioxide; nitrogen; peatlands; Sphagnum